Genomic insights into anthropozoonotic tuberculosis in captive sun bears (Helarctos malayanus) and an Asiatic black bear (Ursus thibetanus) in Cambodia - Officer, Kirsty; Walker, Timothy M.; Cheng, Sokleaph; Heng, Seiha; Hidé, Mallorie; Bañuls, Anne-Laure; Cracknell, Jonathan; Broadis, Nev; Thy, Nhim; Abraham, Sam; Warren, Kris; Jackson, Bethany (Scientific reports, 2024)
Contact between humans and wildlife presents a risk for both zoonotic and anthropozoonotic disease transmission. In this study we report the detection of human strains of Mycobacterium tuberculosis in sun bears and an Asiatic black bear in a wildlife rescue centre in Cambodia, confirming for the first time the susceptibility of these bear species to tuberculosis when in close contact with humans. After genotyping revealed two different strains of M. tuberculosis from cases occurring between 2009 and 2019, 100 isolates from 30 sun bear cases, a single Asiatic black bear case, and a human case were subjected to whole genome sequencing. We combined single nucleotide polymorphism analysis and exploration of mixed base calls with epidemiological data to indicate the evolution of each outbreak. Our results confirmed two concurrent yet separate tuberculosis outbreaks and established a likely transmission route in one outbreak where the human case acted as an intermediatory between bear cases. In both outbreaks, we observed high rates of transmission and progression to active disease, suggesting that sun bears are highly susceptible to tuberculosis if exposed under these conditions. Overall, our findings highlight the risk of bi-directional transmission of tuberculosis between humans and captive bears in high human tuberculosis burden regions, with implied considerations for veterinary and public health. We also demonstrate the use of standard genomic approaches to better understand disease outbreaks in captive wildlife settings and to inform control and prevention measures.